Region 8 Trade Fair June 2-7, 1991, Hotel Nikko Manila Garden "Bahandi" treasures from Leyte and Samar. - Region 8 Trade Fair (1991 : Makati, Metro Manila). ([Makati, Metro Manila Market Encouter Secretariat, Bureau of Domestic Trade Promotion, 1991)
An overview of the "Bahandi" Region 8 trade fair held on June 2-7, 1991. The exhibit focuses on the products and crafts made from the Eastern Visayas provinces of Samar Leyte. The exhibitors are sorted by province, with a legend showing whether they sell gifts, toys, and horse wears, fashion accessories, or food. It also lists their contact details, nature of business, legal status, year established, and ingredients used in their products. At the end of the pamphlet is a directory of the Department of Trade and Industry's Region 8 offices.
Cover title.
Keywords: Fairs -- Philippines; Business enterprises -- Philippines -- Eastern Visayas -- Directories; Markets -- Philippines -- Eastern Visayas